High-Speed Surface Temperature Measurement in TiCoated Aluminum During Electron Beam Irradiation; 20th International Symposium on High-Current Electronics (ISHCE) - Teresov A. Anton; Koval T. V. Tamara Vasilievna; Moskvin P. Pavel; Tran My Kim An; Koval N. N. Nikolay Nikolaevich (2018, 2018)
Title screen